The role of the stratospheric polar vortex for the austral jet response to greenhouse gas forcing - Ceppi,P; Shepherd,TG (Geophysical Research Letters, 2019)
Future shifts of the austral midlatitude jet are subject to large uncertainties in climate model projections. Here we show that, in addition to other previously identified sources of intermodel uncertainty, changes in the timing of the stratospheric polar vortex breakdown modulate the austral jet response to greenhouse gas forcing during summertime (December–February). The relationship is such that a larger delay in vortex breakdown favors a more poleward jet shift, with an estimated 0.7–0.8° increase in jet shift per 10-day delay in vortex breakdown. The causality of the link between the timing of the vortex breakdown and the tropospheric jet response is demonstrated through climate modeling experiments with imposed changes in the seasonality of the stratospheric polar vortex. The vortex response is estimated to account for about 30% of the intermodel variance in the shift of the summertime austral jet and about 45% of the mean jet shift.